Determinants of External Debt: The Case of Somalia - Omar, Zahir Mohamed; Ibrahim, Mohamed Isse (Asian Development Policy Review, 2021)
Most emerging countries owe substantial external debt and depend on foreign aid to achieve sustainable economic development. However, this paper’s key purpose is to examine the determinants of Somalia’s external debt. To achieve this, the study used the autoregressive distributed lag (ARDL) model and cointegration test to establish the short- and long‐run relationships during the period from 1980 to 2018. The results show that exchange rate and domestic investment have a significant and positive effect on external debt in the long run, while GDP per capita and government expenditure have a significant negative relationship with external debt; the result in the short run is consistent with the long-run result. The study recommends that the government of Somalia should also concentrate on the profitable sectors (e.g., livestock, fisheries and agriculture) with a view to improving the production and revenue base in order to minimize external debt, government expenditure and imports. Similarly, the expansion of a simpler tax base system and the removal of spending dependence on fiscal stability would boost fiscal balance. Many governments have disguised borrowing by those fiscal measures, which have expanded debt stocks. Foreign debt and aid dependence are not the best ways to ensure a healthy economy, so the Somali governments should start rethinking the allocation of foreign debt and policymakers could promote a strategy and policy to reduce high dependence on debt that has worked in the past.